Le nouveau visage d’une vieille maladie.: Le Pian, la Syphilis Endemique et la Pinta : Les Treponematoses Endemiques - De Schryver, Antoon; Meheus, André (Afrika Focus, 1988)
Yaws and the other endemic treponematoses (bejel or endemic syphilis, pinta) are resurging in many countries of Africa. Today there are more than 2.5 million cases of these diseases, 75% of them in children. More than 100 million additional children are at risk to these disabling and disfiguring infec- tions which destroy tissue and bone. In the 1950’s and 1960’s, through concerted efforts and leadership of UNICEF and WHO, more than 50 million individuals in 46 countries were cured and the diseases were brought under control or even eliminated from large parts of the world. Despite this success, endemic foci remained and in the last ten years there has been an alarming resurgence of the endemic treponematoses, in particular in parts of West and Central Africa. Endemic treponematoses control is based on treatment with single-dose penicillin of the entire treponemal reservoir, and of all clinical cases and their contacts presumed to be incubating the disease. No instances of penicillin-resistance have been documented to date and these infections should be eliminated while the organisms still remain sensitive to penicillin. An endemic treponematoses control programme must be fully integrated into the primary health care system. The persistence of endemic treponematoses in an area is an indicator of failing effectiveness of primary health care. From recent consultations with Member States, WHO Collaborating Centres and expert groups, a consensus regarding the fundamental components of endemic treponematoses control has emerged. Effective disease control requires coordinated and complementary activities by WHO and Member States. The interruption of disease transmission is a feasible and realistic objective for renewed control programmes. KEYWORDS: bejel, control programmes, pinta, primary health, yaws